The Effect of On Time Performance on Passenger Loyalty at Citilink Indonesia Airlines at Sultan Thaha Jambi Airport - Puja Ayu Safitri; Kartika Fajar Nieamah (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
As a result of delays that often occur at Sultan Thaha Jambi Airport, the flight departure and arrival times are not correct. So that it has an influence on customer loyalty. Researchers try to conduct studies based on this basis to determine the impact of punctuality on customer loyalty. During the 2019 Eid Transportation Period, Citiink Indonesia achieved a flight punctuality rate (OTP) of up to 94.88%. This research was conducted with quantitative methods. The data used in this study came from primary data obtained by distributing questionnaires to 200 respondents, which were taken by non-probability sampling. Data were analyzed using simple linear regression, partial test (T test), and coefficient of determination. The results of the study show that On Time Performance has a significant effect on Passenger Loyalty on Citilink Indonesia airlines at Sultan Thaha Airport, Jambi. It can be seen from the results of testing the hypothesis that the t count t table is 10,878 1,972 with a significant value of 0.00 0.05. The results of the calculation of the T test show that H1 is accepted. The results of the coefficient of determination of the On Time Performance variable have an effect of 37.4% on passenger loyalty. From customers (more than 2 times) Citilink Indonesia Airlines On Time Performance can affect Passenger Loyalty with the commitment and comfort provided by the airline with a percentage of more than 8.00%. The majority of Citilink Indonesia airline passengers at Jambi Sultan Thaha Airport prefer flights at lower prices compared to Citilink Airlines which often experience delays with a percentage of more than 6%. This can be seen from the total results of the questionnaire for each variable and the question items.